Stability‐indicating reversed‐phase/normal‐phase high‐performance thin‐layer chromatography technique for the determination of arbidol: Green analytical chemistry viewpoint. Issue 9 (15th June 2021) - Alam, Prawez; Salem‐Bekhit, Mounir M.; Iqbal, Muzaffar; Anwer, Md. Khalid; Alqarni, Mohammed H.; Shakeel, Faiyaz
Abstract: The sensitive and rapid stability‐indicating green reversed‐phase (RP)/routine normal‐phase (NP) high‐performance thin‐layer chromatography (HPTLC) technique has been established for the analysis of arbidol (ADL) from green analytical chemistry viewpoint. The green reversed‐phase analysis of ADL was carried out using RP‐18 silica gel 60 F254S plates. The mobile phase for the green reversed‐phase technique was ethanol/water/ammonia (80:10:10, vol/vol/vol). The routine normal‐phase analysis of ADL was performed using NP‐18 silica gel 60 F254S plates. The mobile phase for the routine normal‐phase technique was hexane/acetone/ammonia (50:45:5, vol/vol/vol). The detection of ADL was performed at 317 nm for both of the techniques. The linearity ranges for the green reversed‐phase and routine normal‐phase techniques were recorded as 40–800 ng/band and 100–600 ng/band, respectively. The proposed reversed‐phase HPTLC technique was also found to be stability‐indicating for the quantification of ADL in the presence of impurities/degradation products. The AGREE scores for green reversed‐phase HPTLC and routine normal‐phase HPTLC techniques were obtained as 0.86 and 0.49, respectively, suggesting the excellent greenness for reversed‐phase HPTLC technique compared with routine normal‐phase HPTLC technique. Overall, the green reversed‐phase HPTLC technique was found to be superior over routine normal‐phase HPTLC technique for the detection of ADL. Abstract : The proposed reversed‐phase high‐performance thin‐layer chromatography (HPTLC) technique is more accurate, precise, robust, and selective for the quantification of arbidol compared with normal‐phase HPTLC technique. The AGREE scores for green reversed‐phase HPTLC and routine normal‐phase HPTLC techniques were obtained as 0.86 and 0.49, respectively, suggesting the excellent greenness for reversed‐phase HPTLC technique compared with routine normal‐phase HPTLC technique.